Was Rooming-In a Safe Approach to Newborns from SARS-Cov-2 Positive Mothers? - Jonet, Joana (2021)
Introduction: Since the emergence of coronavirus disease 2019 (COVID-19) there are limited data describing the risks and specific effects of SARS-CoV-2 in pregnant women and their neonates. To date, there is scarce evidence of in utero transmission, and the risk of perinatal transmission and consequent neonate’s risk of developing COVID-19 during the perinatal period are also unknown. Methods: Since April 2020, universal screening of all pregnant women presenting in labour was implemented in our Hospital. To those positive to SARS-CoV-2 the possibility to room in with the neonate is given. Neonates are tested for SARS-CoV-2 within the first 24 hours and again at 48 hours of life. We made a prospective cohort analysis of all neonates born to mothers positive for SARS-CoV-2 in our hospital from April to November, 2020. Demographics, neonatal and maternal symptoms at the delivery, during hospitalization and once discharged, perinatal routine care and SARS-CoV-2 RT-PCR results were studied. Results: We analyzed 23 mothers positive for SARS-CoV-2. Only eight referred symptoms, mainly headaches, anosmia and ageusia/dysgeusia. The 23 neonates had both SARS-CoV-2 RT-PCR negative. All neonates were born and remained asymptomatic during the 14 days of surveillance time and all were breastfed. Discussion: According to our results, it was safe to allow rooming in in COVID-19 positive mothers since there was no evidence of perinatal infection. This practice is a well-known way to promote early breastfeeding and encourage maternal–infant bonding.